Mental Health, Social Support and Fatalism in Victims of the 2008 Flood in Juarez City Mexico - Oscar Armando Esparza-Del Villar; Rocío García-Hernández; Priscila Montañez-Alvarado; Irene Concepción Carrillo-Saucedo; Marisela Gutiérrez Vega (European Scientific Journal, ESJ, 2018)
This study analyzed symptoms of depression, anxiety, and PTSD in flood victims from Juarez City Mexico. In July of 2008, heavy rain caused floods in several areas in Juarez, where hundreds of people experienced loss of their belongings and damage to their properties. A sample of 756 participants, interviewed in August and September of 2008, were used to compare flood victims and non-victims in levels of depression, anxiety and PTSD. The results indicated that flood victims had statistically significant higher levels in all or the variables mentioned above. In the 392 flood victims, levels of depression, anxiety, and PTSD were correlated with social support and fatalism related factors. It was found that social support and fatalism factors have a small or no relationship with mental health variables of flood victims.